Blood pressure percentiles in a group of Nigerian school age children - Iduoriyekemwen NJ; Sadoh WE; Omuemu VO; Sadoh AE; Iduoriyekemwen NJ; Nwaneri UD; Adigweme IN; Owobo AC; Uduebor JO; Ekpebe PA (Nigerian Journal of Paediatrics, 2024)
Background: Determination of abnormal blood pressure (BP) in children is dependent on comparison with normal percentile values. The commonly used National Institute of Health (NIH) standard is generated from children outside of Africa. Objective: To develop BP percentile values for Nigerian children based on BP cuff width 40% to 50% of arm circumference. Methods: Subjects were pupils from nine primary schools in Midwestern Nigeria recruited using a multi-stage sampling technique. Their BP was measured using a cuff width of 40 to 50% of arm circumference and cuff length of at least 80% of arm circumference respectively. The mean of two BP readings were taken. Hypertension was defined as systolic and or diastolic BP >95th percentile of the study population.